Hydrogels as functional components in artificial cell systems - Allen,ME; Hindley,JW; Baxani,DK; Ces,O; Elani,Y (Nature Reviews Chemistry, 2022)
Recent years have seen substantial efforts aimed at constructing artificial cells from various molecular components with the aim of mimicking the processes, behaviours and architectures found in biological systems. Artificial cell development ultimately aims to produce model constructs that progress our understanding of biology, as well as forming the basis for functional bio-inspired devices that can be used in fields such as therapeutic delivery, biosensing, cell therapy and bioremediation. Typically, artificial cells rely on a bilayer membrane chassis and have fluid aqueous interiors to mimic biological cells. However, a desire to more accurately replicate the gel-like properties of intracellular and extracellular biological environments has driven increasing efforts to build cell mimics based on hydrogels. This has enabled researchers to exploit some of the unique functional properties of hydrogels that have seen them deployed in fields such as tissue engineering, biomaterials and drug delivery. In this Review, we explore how hydrogels can be leveraged in the context of artificial cell development. We also discuss how hydrogels can potentially be incorporated within the next generation of artificial cells to engineer improved biological mimics and functional microsystems.